Sodium Glucose Cotransporter-2 (SGLT-2) Inhibitor Related Diabetic Ketoacidosis - Kula, Atay Can; Hoca, Emre; Ahbab, Suleyman; Ataoglu, H. Esra (European Scientific Journal, ESJ, 2019)
Diabetic ketoacidosis is a rare but serious and life-threatening acute complication of diabetes mellitus. It is characterized by ketoacidosis with other findings and should be treated immediately. In this case, a 33-year-old diabetic patient who admitted to the emergency department with diabetic ketoacidosis is presented. The patient was prescribed empagliflozin (sodium glucose cotransporter inhibitor-2) a month ago. The SGLT-2 inhibitors have been approved for use in the treatment of type 2 DM and are still not used in the treatment of type 1 DM. There are such reports of unusual side effects related SGLT-2 inhibitors, in the literature and among them, ketoacidosis is a rare and important side effect.